Immunosuppressive and Cytotoxic Potential of Flavonoids from Medicinal Plants: Preliminary Investigation for Anticancer Activity - Amit Gupta; Revati N Chavan (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2017)
Introduction: Attention related to scientifi c and research interest towards naturally derived compounds from medicinal plant products as they are considered to have less toxic side effects as compared to current treatments such as chemotherapy. Medicinal plant produces naturally occurring secondary metabolites especially fl avonoids which are being investigated for their anticancer activities leading to the development of new clinical drugs. Objective- In this regard, immunological studies were conducted to investigate its immunosuppressive and cytotoxic activity of fl avonoids from the leaves of Calotropis gigantea, Adhatoda vasica and Artocarpus integrifolia on human whole blood and peripheral blood mononuclear cells (PBMC) against hepatitis B vaccine containing surface antigen (HBsAg). Methods: for these studies, our group evaluated variable doses of fl avonoids extracted from the leaves of Calotropis gigantea, Adhatoda vasica and Artocarpus integrifolia and estimated blood counts (lymphocytes, monocytes and granulocytes count using fl ow cytometry); nitric oxide production (using Griess reagent assay) and proliferation assay against HBsAg. Results: The results of these studies claimed that these fl avonoids showed sudden decline in monocytes and granulocytes count; nitric oxide production and also showed its cytotoxicity in the form of proliferation at higher doses as compared to control. Conclusion: Overall, these fl avonoids showed immunosuppressive as well as cytotoxic effect against HBsAg and also probable candidate for anticancer agent.